The changes in physical and chemical properties of soil during progressive succession of vegetation at Me Linh station for biodiversity, Vinh Phuc province - Ngoc Mai, Ma Thi; Tan, Le Dong (Academia Journal of Biology, 2014)
The changes in physical and chemical properties of soil during progressive succession of vegetation at Me Linh station for biodiversity, Vinh Phuc province